2007
DOI: 10.1007/s00216-007-1603-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring magnesium, calcium and potassium isotope ratios using ICP-QMS with an octopole collision cell in tracer studies of nutrient uptake and translocation in plants

Abstract: The ability of a quadrupole-based ICP-MS with an octopole collision cell to obtain precise and accurate measurements of isotope ratios of magnesium, calcium and potassium was evaluated. Hydrogen and helium were used as collision/reaction gases for ICP-MS isotope ratio measurements of calcium and potassium in order to avoid isobaric interference with the analyte ions from (mainly) argon ions 40Ar+ and argon hydride ions 40Ar1H+. Mass discrimination factors determined for the isotope ratios 25Mg/24Mg, 40Ca/44Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…ICP-MS calibration and test methods have been developed and applied over years of investigations of liquid and solid phase samples [14,[16][17][18][19][20][21][38][39][40][41]. These methods include EPA Method 6020A and EPA Compendium Method IO-3.5, which describe calibration, standardization, test protocol, data analysis, and quality control procedures.…”
Section: Methods Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…ICP-MS calibration and test methods have been developed and applied over years of investigations of liquid and solid phase samples [14,[16][17][18][19][20][21][38][39][40][41]. These methods include EPA Method 6020A and EPA Compendium Method IO-3.5, which describe calibration, standardization, test protocol, data analysis, and quality control procedures.…”
Section: Methods Theorymentioning
confidence: 99%
“…The series of chilled impingers contain various corrosive materials and must be handled and prepared in a meticulous fashion. Furthermore, sample collection and digestion may require 4 h or more, depending on the detection limit of the analyzing equipment and the initial concentration of Spectrochimica Acta Part B 85 (2013) [34][35][36][37][38][39][40][41][42][43][44] material in the process gas. The long-duration sample collection time produces quantitative analysis reflecting time-averaged concentrations, which will mask shorter duration spikes in concentration that may be of interest in some analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The authors stated that, despite the successful removal of 40 Ar + interference by the reaction with methane, it was not possible to measure 44 Ca/ 40 Ca or 42 Ca/ 40 Ca ratios with a precision better than 0.5% RSD, most likely due to uncertainties associated with the detection system when measuring high count rates. Simpson et al (2005) and Becker et al (2008) employed an ICP‐MS Agilent 7500c series equipped with an rf‐octopole cell, and hydrogen as reaction gas, (octopole reaction system—ORS). Simpson et al (2005) compared the performance of a double‐focusing sector‐field ICP‐MS Element1 and an ICP‐MS with octopole collision cell, and found that isotope ratios of 44 Ca/ 42 Ca measured with octopole collision cell ICP‐MS were much more precise (RSD of 0.4%) compared to those measured with Element1 (RSD of 1.5%).…”
Section: Analytical Methods For Precise Isotope Analyses Of Calciummentioning
confidence: 99%
“…Simpson et al (2005) attributed the worse precision to the application of a higher mass resolution that deteriorated peak shapes, and to that fact that the plasma ion source of the Element1 was much less robust (therefore, much more noisy). Becker et al (2008) measured 40 Ca/ 44 Ca and 42 Ca/ 44 Ca isotope ratios with a precision of 0.43% and 0.19%, respectively. The reported results for Ca had significantly higher relative standard deviations compared to those obtained by Bandura, Baranov, and Tanner (2000) for Fe or Pb isotope ratios; nevertheless, the performance of those techniques was satisfactory for studies with stable Ca isotopes, where a measurement precision better than 1% is usually required (Stürup, 2002).…”
Section: Analytical Methods For Precise Isotope Analyses Of Calciummentioning
confidence: 99%
See 1 more Smart Citation